Religious Moderation from a Legal Perspective in Indonesia to Prevent the Infiltration of Radicalism and Extremism in Higher Education Institutions - Yetno, Alfred; Cristiana, Edelweisia (Jurnal Ilmu Hukum Tambun Bungai, 2025)
To build a strong character within Indonesian society, particularly in the higher education environment, through the implementation of religious moderation today, it requires the involvement and collective commitment of the entire academic community, including lecturers, students, and educational staff. The implementation of religious moderation has a strong legal foundation, as it aims to prevent the spread of radicalism and extremism ideologies that are contrary to Indonesian laws and regulations, such as Law Number 12 of 2022 concerning Criminal Acts of Terrorism, as well as other legal provisions that prohibit actions threatening national security and the integrity of the Unitary State of the Republic of Indonesia (NKRI). This effort is carried out through the strengthening of national commitment based on the four national pillars: Pancasila, the 1945 Constitution, the Unitary State of the Republic of Indonesia (NKRI), and Bhinneka Tunggal Ika, all of which possess legal legitimacy as the foundation of national and state life. Secondly, the strengthening of attitudes of tolerance and respect for differences is pursued in accordance with the principles of human rights law guaranteed by the constitution, particularly Articles 28E and 28I of the 1945 Constitution. Thirdly, fostering a way of religious practice that respects the traditions and local cultures of Indonesia’s diverse society also reflects the protection of cultural rights within the framework of national law. The method used in this research is a qualitative method with a literature study approach, which enables the exploration of various legal instruments and government policies related to religious moderation in the higher education environment